2003
DOI: 10.1002/adma.200304621
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Responsive Synthetic Hydrogels

Abstract: OLED Fabrication and Measurements: Pre-patterned indium tin oxide (ITO) substrates with an effective individual device area of 3.14 mm 2 were cleaned by sonication in a detergent solution for 3 min and then washed with large amount of doubly distilled water. Further sonication in ethanol for 3 min followed before blowing dry with a stream of nitrogen. The ITO substrates were then treated with O 2 plasma for one minute before being loaded into the vacuum chamber. The organic layers were deposited thermally at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
415
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(424 citation statements)
references
References 37 publications
6
415
2
1
Order By: Relevance
“…In tissue engineering applications where cell trafficking within the hydrogel is desirable, click alginate hydrogels could be processed using existing techniques to introduce microscale porosity to the hydrogels [50,51]. Alternatively, click alginate polymers could be crosslinked using tetrazine or norbornene-modified matrix metalloproteinase-degradable peptide sequences to allow cell-mediated degradation [29,52]. The use of partially oxidized alginate polymers would also allow degradation of the hydrogel over controlled time scales for in vivo tissue engineering applications [20,53].The tissue compatibility and stability of click alginate hydrogels could make it particularly useful for applications where isolation from host immune cell infiltration is required [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In tissue engineering applications where cell trafficking within the hydrogel is desirable, click alginate hydrogels could be processed using existing techniques to introduce microscale porosity to the hydrogels [50,51]. Alternatively, click alginate polymers could be crosslinked using tetrazine or norbornene-modified matrix metalloproteinase-degradable peptide sequences to allow cell-mediated degradation [29,52]. The use of partially oxidized alginate polymers would also allow degradation of the hydrogel over controlled time scales for in vivo tissue engineering applications [20,53].The tissue compatibility and stability of click alginate hydrogels could make it particularly useful for applications where isolation from host immune cell infiltration is required [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the hydrogels are formed by reacting a multifunctional polymer (for example, PEG macromers with vinyl sulphones or acrylates) with end groups of proteasesensitive peptides (for example, thiols from cysteine moieties), where cells and molecules can be encapsulated during gelation. The remodelling of hydrogels by cells was observed for hydrogels where both sequences for adhesion and degradation were present 50 , with degradation rates controlled by crosslink density and peptide specificity 51 . This approach has been used in numerous cases to permit cell-mediated degradation of hydrogels, leading to engineered constructs for tissues such as bone and vascular structures 49,52 , including examples of the incorporation of growth factors released via cellular cues 53 .…”
Section: Hydrogels That Degrade With Timementioning
confidence: 99%
“…Previous work has demonstrated that network degradation can be used to control drug release temporally and influence tissue formation [1,2,6,9,11,14,20,21,[25][26][27][28][29]. Degradation in covalently crosslinked polymeric biomaterials has been achieved through hydrolytic cleavage of esters and anhydrides and also through enzymatically induced cleavage of select peptide sequences that have been incorporated into the material [2,22,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%